Our Collective Needs and Strengths: Urban AI/ANs and the COVID-19 Pandemic - Maudrie, Tara L.; Lessard, Kerry Hawk; Dickerson, Jessica; Aulandez, Kevalin M. W.; Barlow, Allison; O’Keefe, Victoria M. (Frontiers in Sociology, 2021)
The COVID-19 pandemic has raised national consciousness about health inequities that disproportionately impact American Indian/Alaska Native (AI/AN) communities, yet urban AI/AN communities continue to remain a blind spot for health leaders and policymakers. While all United States cities have been the traditional homelands of AI/AN peoples since time immemorial, urban AI/ANs are consistently excluded in local and national health assessments, including recent reports pertaining to COVID-19. Today the majority of AI/ANs (71%) live in urban areas, and many cities have strong Urban Indian Health Programs (UIHPs) that provide space for medical care, community gatherings, cultural activities, and traditional healing. Many of these UIHPs are currently scrambling to meet the needs of their AI/AN service communities during the pandemic. While the COVID-19 pandemic brought new sources of funding to UIHPs, the lack of local AI/AN data and arbitrary funding restrictions precluded some UIHPs from addressing their communities’ most immediate challenges such as food and economic insecurities. Despite these challenges, urban AI/AN communities carry the historical resilience of their ancestors as they weave strong community networks, establish contemporary traditions, and innovate to meet community needs. This article focuses on the experiences of one UIHP in Baltimore City during the COVID-19 pandemic to illustrate present-day challenges and strengths, as well as illuminate the urgency for tailored, local data-driven public health approaches to urban AI/AN health.